A comparative study on the effect of orthodontic bracket debonding techniques on enamel - Escalante, Ma. Georgia C.
Although there are a wide variety of orthodontic bracket debonding techniques, most orthodontists use the traditional method of debonding without giving much thought to its effect on enamel. This study was done to compare two techniques of debonding procedures that will produce surface characteristics closest to that of natural enamel. Two different debonding techniques were employed on three sets of freshly extracted premolars, viewing the enamel surface through SEM after each stage of the debonding process. The first technique was resin removal with a diamond bur at low speed and polishing with rubber cup and pumice. The second technique was resin removal with 30-fiuted carbide bur at high speed and polishing with brown and green cups. The results were recorded in photomicrographs and graded according to the pattern and depth of scratches and how much resin remained on enamel. Both methods revealed clinically acceptable results but with enamel scarring. The first method however left some retained resin while the second method left no retained resin. The recommended orthodontic bracket debonding technique is therefore resin removal with a 30-fluted carbide bur at high speed and polishing with brown and green cups.